Features of impaired seminiferous tubule differentiation are associated with germ cell neoplasia in adult men surgically treated in childhood because of cryptorchidism. - Marek Sosnowski; Elzbieta Oszukowska; Wojciech Kuzański; Jolanta Slowikowska-Hilczer; Anna Gumińska; Katarzyna Marchlewska; Renata Walczak-Jedrzejowska; Jerzy Niedzielski; Krzysztof Kula (Folia Histochemica et Cytobiologica, 2008)
Seminiferous tubule differentiation was related to the occurrence of germ cell neoplasia in 38 men, aged 17-47, treated surgically in childhood for cryptorchidism. Tissues from 46 testes obtained from biopsies taken as a neoplastic preventive procedure or whole testes removed because of GCT were evaluated quantitatively. Paraffin sections were treated with antibodies against placental like alkaline phosphatase (PLAP), a marker of germ cell neoplasia, and cytokeratin 18 (CK-18), a marker of immature Sertoli cells. Quality of spermatogenesis and number Leydig cells were assessed with a score count. Seminiferous tubules diameter, thickness of basal membrane and size of intertubular spaces were measured with image analysis software. In 17.4% of testes spermatogenesis was normal (9.9 points) (N) and neoplasia was not found there. In the other 38 specimens (83%) spermatogenesis was abnormal (A). When spermatogenesis was arrested or when germ cells were absent (3.7+/-1.8 points), neoplastic lesions were found in 13.1% of the specimens. In A group 5.1+/-7.1% of tubules contained immature Sertoli cells, while in N they were not found. Tubular diameter was significantly lower in A (161.5+/-31.8 microm) than in N (184.6+/-24.3 microm) and the percentage of seminiferous tubules with the thickening of tubular basal membrane was also greater in A. Intertubular spaces were significantly larger in A (49.9+/-18.6%) in comparison to N group (32.6+/-12.5%). Mean number of Leydig cells was similar in both groups. To conclude, in most of the formerly cryptorchid testes, despite surgical treatment, impaired seminiferous tubules differentiation is predominant. Germ cell neoplasia is present in testes with retarded seminiferous tubules differentiation. Retardation of seminiferous tubule differentiation consists of inhibited spermatogenesis, presence of tubules with immature Sertoli cells, decreased tubular diameter, increased thickness of basal membrane and enlarged intertubular spaces. Examination of testicular biopsy with respect to the state of seminiferous tubule differentiation may be helpful to predict the appearance of germ cell neoplasia in adult men with cryptorchidism in anamnesis. Orchiopexy of cryptorchid testes may not prevent the occurrence of features of testicular dysgenesis and the associated germ cell neoplasia.